Survey on Data Center Network for Cloud Computing - Xuan Luo; Tong Ye; Yaohui Jin (Dianxin kexue)
Data center network has faced several challenges from the arising of cloud computing.Along with the continuous expansive bandwidth requirements，data center network also should provide network isolation and service guarantee for each tenant.Current researches focued on the physical network，network virtualization and service guarantee were introduced.